2012
DOI: 10.1016/j.bbrc.2012.03.047
|View full text |Cite
|
Sign up to set email alerts
|

Neuronal glycosylation differentials in normal, injured and chondroitinase-treated environments

Abstract: Glycosylation is found ubiquitously throughout the central nervous system (CNS).Chondroitin sulphate proteoglycans (CSPGs) are a group of molecules heavily substituted with glycosaminoglycans (GAGs) and are found in the extracellular matrix (ECM) and cell surfaces. Upon CNS injury, a glial scar is formed, which is inhibitory for axon regeneration.Several CSPGs are upregulated within the glial scar, including NG2, and these CSPGs are key inhibitory molecules of axonal regeneration. Treatment with chondroitinase… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
17
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 33 publications
0
17
0
Order By: Relevance
“…Only targeting the intracellular IF protein could suppress the GFAP expression and reduce physical obstacles, but the newborn axons would stop growing once meeting the ECM [21,22]. Also, only inhibiting the extracellular CSPG expression may result in a fragile capacity of newborn axon growth, rendering them unable to pass through dense scar tissue and thus limiting neurologic recovery [23,24]. In our previous research, we reported that the use of antisense vimentin complementary DNA and chondroitinase ABC for treating SCI can effectively inhibit glial scar and shrink the cystic cavities area.…”
Section: Discussionmentioning
confidence: 98%
“…Only targeting the intracellular IF protein could suppress the GFAP expression and reduce physical obstacles, but the newborn axons would stop growing once meeting the ECM [21,22]. Also, only inhibiting the extracellular CSPG expression may result in a fragile capacity of newborn axon growth, rendering them unable to pass through dense scar tissue and thus limiting neurologic recovery [23,24]. In our previous research, we reported that the use of antisense vimentin complementary DNA and chondroitinase ABC for treating SCI can effectively inhibit glial scar and shrink the cystic cavities area.…”
Section: Discussionmentioning
confidence: 98%
“…SSEA-3 and -4 glycolipids used to identify human embryonic stem cells 23 24 . Cell surface glycosylation alters temporally and spatially during differentiation, development and disease 24 25 26 and reflects the cell phenotypic and tissue biological status 27 . Glycosylation has numerous biological roles, including cellular homing and trafficking, signalling, cell-cell and cell-ECM communication and adhesion 24 26 28 .…”
mentioning
confidence: 99%
“…Cell surface glycosylation alters temporally and spatially during differentiation, development and disease 24 25 26 and reflects the cell phenotypic and tissue biological status 27 . Glycosylation has numerous biological roles, including cellular homing and trafficking, signalling, cell-cell and cell-ECM communication and adhesion 24 26 28 . Glycans exert their biological effects in vivo via lectins, carbohydrate-binding proteins 24 26 .…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…NG2 has been reported to be involved in inhibition of axonal regeneration after SCI [40][41][42]. The use of ChABC enzymes to digest the glycosaminoglycan chains of NG2 and related proteoglycans promoted neurite outgrowth and axonal growth [43][44][45][46]. Transduction with a lentiviral vector encoding ChABC has been shown to promote functional recovery in the forelimb post-SCI by reducing chondroitin sulphate chains and enhancing axonal growth after a cervical contusion injury [22].…”
Section: Introductionmentioning
confidence: 99%